2018
DOI: 10.1094/pdis-02-18-0282-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Alternaria Species Associated with Moldy Core of Apple in Chile

Abstract: Moldy core (MC) of apple is an important disease in Chile, with prevalence observed between 4 and 46% in Fuji, Oregon Spur Red Chief, and Scarlet apple in the 2014-15 and 2015-16 growing seasons. However, there is no information on the identity of the causal agents associated with MC in Chile. The analysis of 653 MC fruit revealed the presence of several genera of filamentous fungi. However, species of Alternaria (67.7%) were by far the most frequently fungi isolated. In total, 41 Alternaria isolates were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…ITS is most efficient for fungal identification up to species level (Seena et al 2010;Schoch et al 2012;Al-Nadabi et al 2018). The ITS regions have been broadly B I O D I V E R S I T A S 22 (2): 615-623, February 2021 616 used in molecular phylogeny and taxonomical studies as they can be readily amplified using small quantities of DNA (Schoch et al 2012;Elfar et al 2018). It includes small and large ribosomal subunits sequences (ITS1, ITS2) on DNA and gives a good resolution at family, genus, or species level hence proved to be an ideal (Asemaninejad et al 2016;Řezáčová et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ITS is most efficient for fungal identification up to species level (Seena et al 2010;Schoch et al 2012;Al-Nadabi et al 2018). The ITS regions have been broadly B I O D I V E R S I T A S 22 (2): 615-623, February 2021 616 used in molecular phylogeny and taxonomical studies as they can be readily amplified using small quantities of DNA (Schoch et al 2012;Elfar et al 2018). It includes small and large ribosomal subunits sequences (ITS1, ITS2) on DNA and gives a good resolution at family, genus, or species level hence proved to be an ideal (Asemaninejad et al 2016;Řezáčová et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that Dothideomycetes and Sordariomycetes were significant classes belonging to Ascomycota. Several fungal pathogens causing apple diseases are in these classes [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. For example, Alternaria [ 70 , 75 ] and Epicoccum [ 70 ] belonging to Dothideomycetes have been described as causal agents of moldy core in apple.…”
Section: Discussionmentioning
confidence: 99%
“…Several fungal pathogens causing apple diseases are in these classes [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. For example, Alternaria [ 70 , 75 ] and Epicoccum [ 70 ] belonging to Dothideomycetes have been described as causal agents of moldy core in apple. Acremonium , belonging to the Sordariomycetes, is the causal agent of black and brown spot diseases [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keissl. isolated from Apple (Elfar et al 2018). To confirm the pathogenicity on Italian ryegrass, healthy plants (8-week-old) of cultivar Splendor grown in five pots filled with potting soil were spray-inoculated with conidial suspension…”
mentioning
confidence: 99%